Legg-Calvé-Perthes Disease in Clinical Case Studies in Dogs - Szabóová Renáta; Bajczer Csilla (Folia Veterinaria)
Legg-Calvé-Perthes disease (LCPD) is a degenerative disorder of the femoral head bone with a genetic basis which generally occurs in predisposed small dog breeds (up to 12 kg) at a young age (4–10 months). The aim of this study was to present an overview of this disease, the most common clinical symptoms and to describe methods of diagnosis and therapy of LCPD in dogs. This involved a follow-up of patients, dogs (n = 43; 20 males and 23 females) brought to the veterinary clinic in Hungary with suspicion of LCPD, where they were subjected to clinical, orthopaedic and radiographic examination and then to the most suitable conservative or surgical treatment. The most characteristic clinical symptom – lameness ‒ expressed by lameness grade (from 1 to 5), was monitored in all patients, especially those with grade 4 (n = 26). Additional clinical symptoms, such as response to manipulation (n = 42), pain on palpation (n = 33), weight-bearing (n = 2), muscle atrophy (n = 17) and crepitation (n = 24), were checked in the dogs. The prevalence of the unilateral form of LCPD in the pelvic limbs was observed in 38 patients (88.37 %) and the bilateral LCPD form appeared in 5 patients (11.63 %). Based on the Ljunggren’s score the degree of hip joint damage was observed in most LCPD patients with score 4 (n = 22; 51.10 %). Following the diagnosis, it was necessary to decide on the therapy, conservative or surgical (ostectomy), with elimination of painful symptoms and subsequent long-term postoperative rehabilitation as well as the improvement of the patient’s health status.